Development cycle of pecan - Phenological scale - De Marco, Rudinei (2021)
The knowledge of phenology allows the identification of the physiological moment to which the plant's needs are associated. Once met, it will make it possible to define the most suitable periods for carrying out cultural and management treatments. In this context, this work's objective was to describe the BBCH scale for pecan to standardize the studies carried out on the subject and assist in recognizing the main phenological stages of the species in the Rio Grande do Sul state – Brazil and Uruguay. First, we describe the phenological stage using different cultivars over two locations and two cycles. After, based on the original BBCH scale, the phenological scale for pecan was described, totaling 34 stages that allow us to identify the main stages of development through a precise and simplified approach. Furthermore, this scale allows standardizing future protocols on the specific culture through the coding used.